Linking in, lifting up: how LinkedIn use shapes self-esteem through social comparison processes - Tan, Beverley Ling Xuan (Nanyang Technological University, 2024)
Social networking sites provide innumerable social comparison opportunities. Recent studies explored social comparison and its effects across professional networking sites such as LinkedIn. However, the impact of LinkedIn use on one’s self-esteem (SE) remains a crucial yet underexplored area. Our study fills this gap through a cross-sectional survey of 487 university students in Singapore to understand the relationship between frequency of LinkedIn use (FL) and SE, while accounting for the influence of both upward (USC) and downward (DSC) social comparison (as mediators) as well as social comparison motivations (SCM as moderators). While results revealed that FL does not directly influence SE, FL decreased one’s SE through USC when they have low levels of modelling (MM) as comparison motivation. The study also found that USC only had an influence on SE when individuals were motivated for comparison to model or self-enhance (SM). Results are discussed in terms of extant research and their implications for LinkedIn users’ well-being with actionable insights postulated for platform designers and educators.